Analysis of Social Return on Investment (SROI) in Corporate Social Responsibility (CSR) of BPKH x BMM through the present value approach to the Free Cataract Surgery Program for 100 West Java residents in 2023 - Karmila Eka Putri; Tri Wahyu Oktavendi (PT. Publikasiku Academic Solution, 2024)
The high rate of blindness due to cataracts in Indonesia, especially in West Java, has prompted the Hajj Financial Management Agency (BPKH) in collaboration with Baitulmaal Muamalat (BMM) to carry out a free cataract surgery program for 100 West Java residents in 2023. This study aims to analyze the effectiveness of the program through the Social Return on Investment (SROI) approach that considers social, economic, and environmental impacts. The qualitative approach was used to analyze the social impact of the Free Cataract Surgery program in more detail, while the descriptive quantitative approach was used to measure social return on investment (SROI) and analyze the results of social impact calculations. The results of the analysis show a SROI ratio of 2.08, which means that every Rp1.00 invested generates social benefits worth Rp2.08. This program not only has a positive impact in the form of improving community health and productivity, but also economic benefits for stakeholders such as clinics, MSMEs, and medical personnel. The results of the study provide an overview of the evaluation that can be used to improve the sustainability of similar programs in the future.